Correlation between patient satisfaction with the use of a removable retainer and compliance: a correlational study - Omar, Naufal Halef; Sayuti, Elih; Laviana, Avi (Universitas Padjadjaran, 2025)
Introduction: Removable retainers are one of the devices used after active orthodontic treatment. Their use requires patient compliance with the prescribed wearing time; however, many patients remain non-compliant due to dissatisfaction with the removable retainer. This study aims to analyze the correlation between patient satisfaction with the use of a removable retainer and compliance. Methods: The research method used is correlational analysis. This study uses primary data collected through online questionnaires via Google Forms to patients of the Universitas Padjadjaran Dental Hospital, aged 18-45 years, who have undergone orthodontic treatment with fixed appliances followed by the use of removable retainers for 1-24 months. The total sample consists of 38 subjects. The seven questions assessing satisfaction were used to calculate each respondent’s total satisfaction score. The data were analyzed using the Spearman correlation test. Results: The data show that the majority of research subjects were satisfied (44.7%), and more than half were classified as compliant (57.9%). The correlation between patient satisfaction while using a removable retainer and compliance with its use resulted in a correlation coefficient of 0.447, with a significance value of 0.002 (p value<0.05). Conclusion: There is a moderately strong positive correlation between patient satisfaction with a removable retainer and patient compliance in wearing it.